2021
DOI: 10.1101/2021.03.26.437219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overabundance ofAsaiaandSerratiabacteria is associated with deltamethrin insecticide susceptibility inAnopheles coluzziifrom Agboville, Côte d’Ivoire

Abstract: Background: Insecticide resistance among mosquito species is now a pervasive phenomenon, which threatens to jeopardise global malaria vector control efforts. Evidence of links between the mosquito microbiota and insecticide resistance is emerging, with significant enrichment of insecticide degrading bacteria and enzymes in resistant populations. Using 16S rRNA amplicon sequencing, we characterised and compared the microbiota of Anopheles (An.) coluzzii in relation to their deltamethrin resistance and exposure … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 89 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Strikingly, Serratia abundance is dramatically reduced in Banfora-R compared to Banfora-S and is in agreement with a recent discovery in Côte D’Ivoire showing that this bacteria is strongly associated with pyrethroid susceptibility in An. coluzzii 27 . Further study is needed to determine the relative contribution of these individual bacteria to the insecticide resistance phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, Serratia abundance is dramatically reduced in Banfora-R compared to Banfora-S and is in agreement with a recent discovery in Côte D’Ivoire showing that this bacteria is strongly associated with pyrethroid susceptibility in An. coluzzii 27 . Further study is needed to determine the relative contribution of these individual bacteria to the insecticide resistance phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent induction study using sub-lethal pyrethroid exposure has shown large scale changes in the transcriptome including huge down-regulation of the oxidative phosphorylation pathway post-exposure 15 . Sub-lethal exposure is also important in the context of a changing microbiome, which has been shown to be modified upon exposure 26 and several bacterial species have been linked to the resistance phenotype 27,28 .…”
Section: Introductionmentioning
confidence: 99%